Analysis of Narrative Strategies in Independent Non-Fiction Narrative Podcasts in Ibero-America - Rodríguez-Ortiz, Raúl (2025)
This study analyses the narrative strategies employed in 11 independent narrative non-fiction podcasts from seven Ibero-American countries: Argentina, Brazil, Spain, Portugal, Colombia, Chile, and Mexico. The research concentrates on identifying the primary narrative trends applied within this genre of audio journalism, focusing on how the role of the narrator and the structure of the story boost credibility and listener engagement. The methodology combines semi-structured interviews with 16 podcast producers and content analysis of 73 episodes to explore how these podcasts shape their narrative approaches. The results reveal that these podcasts use various journalistic subgenres, including interviews, sound chronicles a recognised genre within narrative and radio journalism in Ibero-American, and other more artistic or experimental formats such as radio features, along with narrative structures like episodic, Aristotelian, and counterpoint, allowing for diverse forms of storytelling. In addition, the study underscores the incorporation of sound archives, personal life stories, and other audio techniques to enhance the narrative’s depth and emotional resonance. These elements contribute to producing socially relevant stories that often challenge stereotypes and address underrepresented voices in society. Ultimately, this research highlights the role of independent non-fiction podcasts in the evolution of audio journalism in Ibero-America.